2014
DOI: 10.1155/2014/762514
|View full text |Cite
|
Sign up to set email alerts
|

Association ofHelicobacter pyloriand iNOS Production by Macrophages and Lymphocytes in the Gastric Mucosa in Chronic Gastritis

Abstract: Helicobacter pylori is one of the most common causes of chronic gastritis. With the development of the disease cellular inflammatory infiltrates composed of lymphocytes, plasma cells, and macrophages are formed in epithelium and lamina propria of the stomach. These cells are capable of secreting a number of active substances, including inducible nitric oxide synthase (iNOS). We examined the relationship between H. pylori and secretion of iNOS by cells of inflammatory infiltrates in chronic gastritis by light m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 16 publications
0
18
0
1
Order By: Relevance
“…Granulocyte and macrophage infiltration is increased at the ulcer margin, and it has been suggested that this could be the major source of increased COX‐2 expression that is positively regulated by IL‐1β and TNF‐α (Takahashi et al ., ; Shigeta et al ., ; Jackson et al ., ). Moreover, the increased infiltration of macrophages followed by an up‐regulated NOS expression has been observed during the development of chronic gastritis (Cherdantseva et al ., ). We observed that CORM‐2 decreased mRNA and protein expression of pro‐inflammatory factors such as iNOS, as well as COX‐2.…”
Section: Discussionmentioning
confidence: 97%
“…Granulocyte and macrophage infiltration is increased at the ulcer margin, and it has been suggested that this could be the major source of increased COX‐2 expression that is positively regulated by IL‐1β and TNF‐α (Takahashi et al ., ; Shigeta et al ., ; Jackson et al ., ). Moreover, the increased infiltration of macrophages followed by an up‐regulated NOS expression has been observed during the development of chronic gastritis (Cherdantseva et al ., ). We observed that CORM‐2 decreased mRNA and protein expression of pro‐inflammatory factors such as iNOS, as well as COX‐2.…”
Section: Discussionmentioning
confidence: 97%
“…While effector immune mechanisms of elimination have not been dissected in depth, the type of immune response elicited may depend on the location and kind of cell that first comes in contact with H. pylori . Colonization of the gastric mucosa by H. pylori induces mixed effector and regulatory immune responses (11). However, its chronic persistence in the host suggests that the regulatory immune responses might predominate over effector mechanisms (1220).…”
Section: Introductionmentioning
confidence: 99%
“…Upon Hp gastric mucosa colonization, an immune response is induced. Mucosal migration of macrophages and lymphocytes producing iNOS also takes place . Once lymphocytes, plasma cells, and macrophages are chemotactically triggered, iNOS is generated, as seen by elevated concentrations of NO metabolites in Hp ‐infected patients .…”
Section: Hp In No‐related Glaucoma Pathophysiologymentioning
confidence: 99%
“…Mucosal migration of macrophages and lymphocytes producing iNOS also takes place . Once lymphocytes, plasma cells, and macrophages are chemotactically triggered, iNOS is generated, as seen by elevated concentrations of NO metabolites in Hp ‐infected patients . Chronic antigenic stimulation, such as by superficial bacterial LPS upon exposure to inflammatory cells, regulates iNOS expression in order to generate NO and RNS.…”
Section: Hp In No‐related Glaucoma Pathophysiologymentioning
confidence: 99%